A tale of two mechanisms: Strain-softening versus strain-hardening in single crystals under small stressed volumes. (1st January 2016) - Bei, H.; Xia, Y.Z.; Barabash, R.I.; Gao, Y.F.
Graphical abstract: Abstract: Pre-straining defect-free single crystals will introduce heterogeneous dislocation nucleation sources that reduce the measured strength from the theoretical value, while pre-straining bulk samples will lead to strain hardening. Their competition is investigated by nanoindentation pop-in tests on variously pre-strained Mo single crystals with several indenter radii (∼micrometer). Pre-straining primarily shifts deformation mechanism from homogeneous dislocation nucleation to a stochastic behavior, while strain hardening plays a secondary role, as summarized in a master plot of pop-in strength versus normalized indenter radius.